Apakah Reksa Dana Syariah Kebal terhadap Gejolak BI Rate dan Inflasi? Studi Kuantitatif di Indonesia - Afrila Mu'arrofah (Commodities, Journal of Economic and Business, 2026)
This study examines the effect of the BI Rate and inflation on the development of Islamic mutual funds in Indonesia, motivated by the continuous growth of Islamic financial instruments and their sensitivity to macroeconomic conditions. The aim of this study is to analyze whether the BI Rate and inflation have a significant effect on the development of Islamic mutual funds in Indonesia.This research uses a descriptive quantitative approach with secondary time series data covering the period 2021–2025. The data were obtained from Bank Indonesia, the Central Statistics Agency (BPS), and the Financial Services Authority (OJK). The data were analyzed using multiple linear regression with SPSS software, along with classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results show that the BI Rate has a negative but insignificant effect on the development of Islamic mutual funds. In contrast, inflation has a negative and significant effect, meaning that an increase in inflation reduces the Net Asset Value (NAV) of Islamic mutual funds. Simultaneously, the BI Rate and inflation significantly affect the development of Islamic mutual funds. The coefficient of determination (R²) of 0.121 indicates that the independent variables explain 12.1% of the variation in Islamic mutual fund development, while the remaining 87.9% is influenced by other factors outside the model.